The ABF1 factor is the transcriptional activator of the L2 ribosomal protein genes in Saccharomyces cerevisiae. - Della Seta, F (1990)
The same factor, ABF1, binds to the promoters of the two gene copies (L2A and L2B) coding for the ribosomal protein L2 in Saccharomyces cerevisiae. In vitro binding experiments and in vivo functional analysis showed that the different affinities of the L2A and L2B promoters for the ABF1 factor are responsible for the differential transcriptional activities of the two gene copies. The presence of ABF1-binding sites in front of many housekeeping genes suggests a general role for ABF1 in the regulation of gene activity.